Effects of sitting postures on risks for deep tissue injury in the residuum of a transtibial prosthetic-user: a biomechanical case study - Portnoy, S.; Siev-Ner, I.; Shabshin, N.; Gefen, A. (Computer methods in biomechanics and biomedical engineering, 2011)
Transtibial amputation prosthetic-users are at risk of developing deep tissue injury (DTI) while donning their prosthesis for prolonged periods; however, no study addresses the mechanical loading of the residuum during sitting with a prosthesis. We combined MRI-based 3D finite element modelling of a residuum with an injury threshold and a muscle damage law to study risks for DTI in one sitting subject in two postures: 30°-knee-flexion vs. 90°-knee-flexion. We recorded skin-socket pressures, used as model boundary conditions. During the 90°-knee-flexion simulations, major internal muscle injuries were predicted (>1000 mm 3 ). In contrast, the 30°-knee-flexion simulations only produced minor injury ( < 14 mm 3 ). Predicted injury rates at 90°-knee-flexion were over one order of magnitude higher than those at 30°-knee-flexion. We concluded that in this particular subject, prolonged 90°-knee-flexion sitting theoretically endangers muscle viability in the residuum. By expanding the studies to large subject groups, this research approach can support development of guidelines for DTI prevention in prosthetic-users.